Heterologous Combination of VSV-GP and NYVAC Vectors Expressing HIV-1 Trimeric gp145 Env as Vaccination Strategy to Induce Balanced B and T Cell Immune Responses - Perdiguero, Beatriz; Gómez, Carmen Elena; García-Arriaza, Juan; Sánchez-Corzo, Cristina; Sorzano, Carlos Óscar S.; Wilmschen, Sarah; von Laer, Dorothee; Asbach, Benedikt; Schmalzl, Christina; Peterhoff, David; Ding, Song; Wagner, Ralf; et al. (Frontiers in Immunology, 2019)
The generation of an HIV/AIDS vaccine able to elicit long-lasting protective immunity remains a major challenge in the HIV field. The modest efficacy (31.2%) of the RV144 phase III clinical trial provided the first evidence that a preventive vaccine against HIV is feasible but highlighted the need for further improvements of HIV/AIDS vaccine candidates, formulations and immunization protocols. In this study, we evaluated in the mouse model the immunogenicity profile induced by different homologous and heterologous prime / boost immunization protocols using the modified rhabdovirus VSV-GP in combination with DNA or poxviral NYVAC vectors, all expressing trimeric membrane-bound Env (gp145) of HIV-1 96ZM651 clade C, with or without purified gp140 protein component. In cultured cells infected with recombinant VSV-GP or NYVAC viruses, gp145 epitopes at the plasma membrane were recognized by human HIV-1 broadly neutralizing antibodies (bNAbs). In immunized mice, the heterologous combination of recombinant VSV-GP and NYVAC vectors improved the induction of both cellular and humoral Env-specific immune responses compared to homologous prime/boost protocols. Specifically, the use of VSV-GP in the prime and NYVAC in the boost induced higher Env-specific T cell (CD4/CD8 T cells and T follicular helper -Tfh- cells) immune responses compared to the use of NYVAC or DNA vectors in the prime and VSV-GP in the boost. Such enhanced T cell responses correlated with an increase of the Env-specific germinal center (GC) B cell population and with a heavily biased Env-specific response towards the Th1-associated IgG2a and IgG3 subclasses, while the other groups showed a Th2-associated IgG1 bias. In summary, our T and B cell population data revealed that VSV-GP-based vectors could be considered as an optimized immunogenic HIV-1 vaccine candidate component when used for priming in heterologous immunizations with the poxvirus vector NYVAC as a boost.